Microstructure Control in 3D Printing with Digital Light Processing. (28th August 2019) - Luongo, A.; Falster, V.; Doest, M. B.; Ribo, M. M.; Eiriksson, E. R.; Pedersen, D. B.; Frisvad, J. R.
Abstract: Digital light processing stereolithography is a promising technique for 3D printing. However, it offers little control over the surface appearance of the printed object. The printing process is typically layered, which leads to aliasing artefacts that affect surface appearance. An antialiasing option is to use greyscale pixel values in the layer images that we supply to the printer. This enables a kind of subvoxel growth control. We explore this concept and use it for editing surface microstructure. In other words, we modify the surface appearance of a printed object by applying a greyscale pattern to the surface voxels before sending the cross‐sectional layer images to the printer. We find that a smooth noise function is an excellent tool for varying surface roughness and for breaking the regularities that lead to aliasing. Conversely, we also present examples that introduce regularities to produce controlled anisotropic surface appearance. Our hope is that subvoxel growth control in stereolithography can lead 3D printing towards customizable surface appearance. The printing process adds what we call ground noise to the printed result. We suggest a way of modelling this ground noise to provide users with a tool for estimating a printer's ability to control surface reflectance. Abstract : Grayscale voxel values in DLP 3D printing enable subvoxel growth control. We use this to control the surface microstructure and thus vary the surface appearance of a printed object as an integrated part of the printing process. To assess the reflectance controllability of our approach, we compare with anisotropic BRDFs and estimate the ground noise added by the printing process.